THE IMPLEMENTATION OF FLIPPED CLASSROOM BY USING TED-ED IN WRITING III CLASS OF THIRD SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY OF UNIVERSITAS BANDAR LAMPUNG - David Ginola; Dameria Magdalena Sidabalok (Universitas Bandar Lampung, 2016)
The objectives of this research were to know how flipped classroom can give an effect to students’ activeness in the class, and to see students’ achievement in experiencing flipped classroom method. In this research, I used the descriptive qualitative method. The kind of method was used to feel the experience the real world, and also to know people’s point of view of a certain phenomenon. It was also used to obtain the truthful, precise, and well-organized explanation about students’ activeness and students’ achievement in experiencing flipped writing class. The research was done at Writing III class of English Education Study Program of Teaching and Training Education of Universitas Bandar Lampung that consisted of twenty-four students. The data were gathered by observation and questionnaire, and those were also analysed by combining the result of observation and questionnaire in several paragraphs. The result of this research showed that when this method firstly implemented, students felt confused of what they should do in the class, but the class in the end ran successfully. From the questionnaire result also showed mostly positive feedbacks in experiencing flipped method, but there are also some negative feedbacks are given in it. The combination of those two instruments is that flipped classroom method is able to facilitate them in writing class. They mostly agreed this method could make them more interested in this class, and it could help them in improving their skills, also it could awake them that they need to be more responsible of their own learning in the class.